2017
DOI: 10.1038/srep45241
|View full text |Cite
|
Sign up to set email alerts
|

Association of aldosterone excess and apnea-hypopnea index in patients with resistant hypertension

Abstract: The present study was to investigate the association of aldosterone excess and apnea-hypopnea index (AHI) in patients with resistant hypertension. Patients with resistant hypertension were enrolled and baseline characteristics including plasma aldosterone concentration (PAC) and 24 h-urine aldosterone levels were collected and compared between groups with different degrees of AHI as assessed by polysomnography. Association of key variables and AHI was then evaluated by univariate and multiple linear regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
4
16
0
2
Order By: Relevance
“…A common cause of RHTN is hyperaldosteronism [35] and several studies have shown a link between high plasma aldosterone concentration and the severity of OSA [36,37]. This can, in part, explain the high prevalence of OSA in RHTN patients.…”
Section: Discussionmentioning
confidence: 99%
“…A common cause of RHTN is hyperaldosteronism [35] and several studies have shown a link between high plasma aldosterone concentration and the severity of OSA [36,37]. This can, in part, explain the high prevalence of OSA in RHTN patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are also intriguing recent reports on the potential role of mineralcorticoid hormones, in particular of aldosterone, in the relationship between OSA and hypertension, Aldosterone is a hormone produced by the outer portion (cortex) of the adrenal gland and is involved in the regulation of water and electrolytes balance in the body. Among patients with resistant hypertension, the occurrence of hyperaldosteronism is significantly associated with the prevalence and severity of OSA (25). In fact, treatment with aldosterone antagonists can reduce not only BP levels, but also the severity of OSA (26).…”
Section: Hormonal and Inflammatory Changesmentioning
confidence: 99%
“…High aldosterone secretion increases the retention of sodium and water in the kidneys and is related to the severity of obstructive sleep apnea and blood pressure level 24, 26, 27. Hypertension in women is more sensitive to sodium intake than in men 27.…”
Section: Discussionmentioning
confidence: 99%